2023
DOI: 10.3390/cancers15143593
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art of Pharmacological Activators of p53 in Ocular Malignancies

Abstract: The pivotal role of p53 in the regulation of a vast array of cellular functions has been the subject of extensive research. The biological activity of p53 is not strictly limited to cell cycle arrest but also includes the regulation of homeostasis, DNA repair, apoptosis, and senescence. Thus, mutations in the p53 gene with loss of function represent one of the major mechanisms for cancer development. As expected, due to its key role, p53 is expressed throughout the human body including the eye. Specifically, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 209 publications
0
5
0
Order By: Relevance
“…p53 mutations are very rare, and MDM4 is overexpressed in UM [ 6 , 11 ]. Therefore, we hypothesized that, similar to its effects in retinoblastoma, CEP-1347 may also effectively suppress MDM4, which is a functional p53 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…p53 mutations are very rare, and MDM4 is overexpressed in UM [ 6 , 11 ]. Therefore, we hypothesized that, similar to its effects in retinoblastoma, CEP-1347 may also effectively suppress MDM4, which is a functional p53 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the development and clinical testing of novel p53-activating small molecules for AML, multiple myeloma, and other hematological malignancies [ 44 ]. Alrizomadlin (APG-115), a small-molecule inhibitor that selectively targets the p53-MDM2 interaction, has been approved by the US FDA and exhibited preliminary antitumor activity in UM [ 6 ]. Additional information on the safety and antitumor effects of these MDM2 inhibitors in UM patients may facilitate the translation of combinations of CEP-1347 and MDM2 inhibitors into the treatment of UM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular pathology is another key feature of the eye in AD patients, as well as in other ocular vascular diseases (i.e., diabetic retinopathy, retinal and macular edema, retinal vein occlusion), where the vascular damage alters nutrient supply and the Aβ clearance, further promoting retinal degeneration [3,[166][167][168][169][170]. Further studies of postmortem retinas have identified the deposition of Aβ aggregates and NFTs in ganglion cells, amacrine cells, horizontal cells, and Müller cells of the inner and outer plexiform layers, which correlate with the cortical cerebral pathology burdens, demonstrating the relationship between ocular-brain pathology and cognitive impairment [57][58][59][60].…”
Section: Signs Of Visual Dysfunction In Alzheimer's Diseasementioning
confidence: 99%